Low prevalence of genotypic drug resistance mutations among antiretroviral-naive HIV type 1 patients in Malaysia - Tee, K.K.; Kamarulzaman, A.; Ng, K.P. (2006)
To assess the prevalence of mutations associated with drug resistance in antiretroviral-naive patients in Kuala Lumpur, Malaysia, genotypic resistance testing was conducted among drug-naive HIV-1 patients attending the University Malaya Medical Center (UMMC) between July 2003 and June 2004. Reverse transcriptase (RT) and protease genes of plasma virions were sequenced from 100 individuals. The majority of the patients were recently diagnosed. Codons 20-255 of the RT and 1-96 of the protease gene were examined for major and minor mutations associated with antiretroviral resistance reported by the International AIDS Society-USA (IAS-USA) Drug Resistance Mutations Group. The prevalence of patients with at least one major mutation conferring drug resistance was 1, with only one patient having a Y181C amino acid substitution in the RT gene that confers high- level resistance to nevirapine and delavirdine. Minor mutations were detected in high prevalence in the protease gene. Amino acid substitutions I13V, E35D, and M36I were associated with CRF01 AE while L63P, V77I, and I93L were associated with subtype B. Baseline prevalence of major mutations associated with resistance to antiretroviral drugs was low among antiretroviral- naive HIV-1 patients, suggesting that routine drug resistance testing may be unnecessary for all individuals newly diagnosed with HIV or all patients beginning antiretroviral therapy.